A nonstiff solution for the stochastic neutron point kinetics equations. (November 2016) - Wollmann da Silva, M.; Vasques, R.; Bodmann, B.E.J.; Vilhena, M.T.
Highlights: We propose an approach to solve the stochastic neutron point kinetics equations. This new approach yields a nonstiff solution for the stochastic formulation. We compute results for stochastic problems with constant, linear, and sinusoidal reactivities. The results show strong agreement with approaches established in the literature. We compute and analyze the first four statistical moments of the solutions. Abstract: We propose an approach to solve the stochastic neutron point kinetics equations using an adaptation of the diagonalization-decomposition method (DDM). This new approach (Double-DDM) yields a nonstiff solution for the stochastic formulation, allowing the calculation of the neutron and precursor densities at any time of interest without the need of using progressive time steps. We use Double-DDM to compute results for stochastic problems with constant, linear, and sinusoidal reactivities. We show that these results strongly agree with those obtained by other approaches established in the literature. We also compute and analyze the first four statistical moments of the solutions.